Circulating fibronectin and fibronectin receptor in children with pertussis. Issue 9 (September 1994) - Torre, D; Giola, M; Zeroli, C; Martegani, R; Bonetta, G; Ferrario, G
Abstract : AIM–To determine concentrations of fibronectin and fibronectin receptor in children with pertussis. METHODS–Concentrations of circulating fibronectin and serum fibronectin receptor were detected in eight children affected by pertussis, eight children with acute upper or lower respiratory tract infections, and in 14 healthy control children. The single radial immunodiffusion technique and a solid phase enzyme immunoassay were used to detect circulating serum concentrations of fibronectin and fibronectin receptor. RESULTS–On admission, a significant decrease in fibronectin was detected in children with pertussis (p = 0.0006). Significant and decreased concentrations of fibronectin were also observed in children with upper or lower respiratory tract infections (p = 0.0002). On the other hand, serum fibronectin receptor concentrations were significantly increased in patients with pertussis, whereas patients with upper or lower respiratory tract infections had normal circulating fibronectin receptor concentrations. CONCLUSIONS–Fibronectin deficiency in children with pertussis may be related to diffusion and deposition of this protein in bronchial and alveolar spaces to limit infection, while increased fibronectin receptor concentrations are probably the expression of T cell activation and cell-mediated immunity during Bordetella pertussis infection.